Migration and Inequality - Black, Richard (World Bank, 2012)
International migration is a powerful symbol of global inequality, whether in terms of wages, labor market opportunities, or lifestyles. Millions of workers and their families move each year across borders and across continents, seeking to reduce what they see as the gap between their own position and that of people in other, wealthier, places. There is a growing consensus in the development field that migration, including international, permanent, temporary and seasonal migration, represents an important livelihood diversification strategy for many in the worlds poorest nations. The paper argues that inequality needs to be defined in broader terms than simply income or wealth. Inequality, like poverty, is multi-dimensional, and can be measured at individual, household, regional and international levels. There are socio-cultural dimensions to inequality as well. Political, economic and social-cultural institutions play a crucial role in the way wealth, power and opportunity are distributed within societies. It should be noted that migration - and especially international migration - is an activity that carries significant risks and costs and does not necessarily reduce inequality in the way intended by many migrants.